Etiological evaluation and the role of plasma exchange treatment in trombotic microangiopathies: A retrospective analysis from Eastern Anatolia - Hidayet, Emine; Erkurt, Mehmet Ali; Sarıcı, Ahmet; Biçim, Soykan; Kuku, Irfan; Berber, Ilhami; Uysal, Ayse (My University, 2022)
The aim is this study was to make the etiological classification of patients diagnosed with TMA in our region and to statistically evaluate the effect of therapeutic plasma\rexchange, which we use in treatment, on laboratory recovery and mortality. In our study, between 2009-2017, 85 patients diagnosed with TMA in our center evaluated\rretrospectively. Thirty- one (36.5%) of our patients were followed up with HELLP, 23 with thrombotic thrombocytopenic purpura (TTP) (27.1%), 20 (23.5%) snake bites,\rand 11 (12.9%) with atypical hemolytic uremic syndrome (aHUS). TPE treatment was performed in all patients. TPE treatment was found effective in patients with HELLP\rsyndrome, TTP and snake bite and statistically significant improvement was obtained in laboratory parameters (p<0.05). However, TPE treatment was not found to be\reffective in the treatment of atipical HUS (p>0.05). Mortality rates were found 9.7%, 21.7%, 27.3%, and 0% in patients with HELLP Syndrome, TTP, aHUS, and snake\rbite, respectively. The primary treatment in HELLP syndrome was termination of pregnancy, it was observed in our study that TPE was effective in TTP, HELLP syndrome\rand snake bites and treatment should be started without delay
Keywords: Genel ve Dahili Tıp; Patoloji; Hematoloji